Integrated River Basin Management Practice Guideline for the IO Table Compilation and CGE Modeling - Deng, Xiangzheng; Wang, Yi.; Wu, Feng.; Zhang, Tao.; Li, Zhihui; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2014)
Establishing multi-scale optimal water allocation modes which takes the enhancement of utilization efficiency as core is a research hotspot for the international water resources management of river basins. This book aims to introduce how to compile the first set of county-level IO tables involving resources and environment accounts with integrated datasets which contains the spatio-temporal data of water and land resources, ecology and social economy in the river basin and to construct an integrated Computable General Equilibrium (CGE) model with resources and environment accounts embedded, which can be used to quantitatively depict the key process parameters of the water-ecology-social economy coupling system. Thus, this book can provide decision support for integrated river basin management, and scientific support for the sustainable development of social economy, eco-environment and water resources.
Introduction and Overview -- Approach of Input-Output Table at Regional Level -- Compilation of Regional Input-Output Table -- The Integrated CGE Model Construction -- Implementation.
Keywords: Environment; Hydrology; Environmental management; Sustainable development; Environmental economics; Environment; Sustainable Development; Hydrology/Water Resources; Environmental Economics; Environmental Management; Water Policy/Water Governance/Water Management; Electronic books